JARINGAN SARAF TIRUAN MEMPREDIKSI PENJUALAN MAKANAN DAN MINUMAN DENGAN MENGGUNAKAN METODE BACKPROPAGATION (STUDI KASUS : PONDOK JATI RESTO BINJAI) - Satria R, Dandi; Simanjuntak, Magdalena; Saragih, Rusmin (STMIK KAPUTAMA, 2021)
Pondok Jati Resto (PJR) is a cafe that provides a variety of foods and beverages that are sold to attract customers or potential customers. The number of food and beverages that have been sold, of course, PJR has data on sales of food and beverages. So far, sales data have only been seen from sales reports. It is of course very unfortunate that other data, for example, such as ordered food and beverage menus, can be used as an evaluation material for food and beverage needs that are often in demand. Food and drink is one of the most needed needs by humans. There are many types of food and drink that are made to fulfill the desire to try a food and drink. Apart from being at home, food and beverages can also be obtained at shops, stalls, restaurants, cafes and so on. The increasing number of population levels and the increasing popularity of the food and beverage business, of course, there are more and more food and beverage sellers circulating in several areas, one of which is Cafe Pondok Jati Resto. The application of artificial neural networks to predict the amount of food and beverages using Matlab software using the Backpropagation method can be applied in predicting the number of food and beverage sales. Based on the analysis process that has been carried out under the artificial neural network system using the Backpropagation method, it can identify data on the number of food and beverage sales, with test results or predictions of the average number of foods per year 20, 5 drinks and 19 snacks.